The Role of Political Factors, Leadership and Human Resource Quality on Budgeting Conflict Management in Local Government - Robinson, Robinson; Herawansyah, Herawansyah; Sundari, Ayun (UNIB Press, 2023)
Abstract: This study aims to provide empirical evidence of the influence of political factors, leadership and the quality of human resources on budgetary conflict management. The population in this study were all members of the Regional House of Representatives (DPRD) and the Regional Government Budget Team (TAPD). This research was tested using multiple linear regression analysis. The results of the study indicate that Political Factors affect budgeting conflict management in the local government and the Quality of Human Resources has an effect on Budgeting Conflict Management. However, leadership has no effect on Budgeting Conflict Management in the local government. The limitation of this research is that in the data collection process, the information provided by respondents through questionnaires sometimes does not show the true opinion, where the results of the study are highly dependent on the results of the questionnaires distributed which allow the tendency for bias to still exist.